Demeanor and police culture: Theorizing how civilian cooperation influences police officers. Issue 4 (12th August 2019) - Pickett, Justin; Nix, Justin
Abstract : Purpose: The purpose of this paper is to revisit classic theoretical arguments regarding the broad effects of civilian demeanor on policing and extend associated findings. Design/methodology/approach: The theoretical framework draws on insights from the literatures on police culture, the group engagement model and fairness heuristic theory. The authors argue that demeanor is best conceptualized as the degree of procedural justice exhibited by civilians toward police. Theoretically, procedurally just cooperation should influence officers' adherence to police culture by affecting their social identification and assessments of civilians' motives and moral deservingness. To test the hypotheses, the authors surveyed sworn officers from a large metropolitan police department in the southeastern USA in the Fall of 2016. Findings: Results reveal that officers use their procedural justice judgments as heuristics to assess civilians' trustworthiness, dangerousness, and moral deservingness, and these judgments influence their policing style. Officers who perceive greater procedurally just cooperation by civilians feel less threatened by the public, are more willing to use procedural justice themselves, and are less supportive of a "tough cop" policing style. Originality/value: The authors propose that: civilian demeanor is best conceptualized as the extent to which civilians exhibit procedural fairness toward the police; and in order for meaningful police reform to occur, it is important to acknowledge the role of civilian demeanor in shaping officers' attitudes, beliefs and behaviors.